Therapeutic hypothermia for neonatal hypoxic ischaemic encephalopathy in sub-saharan africa: a scoping review - Buxton-Tetteh, Naa Akyere (Department of Paediatrics and Child Health, 2025)
There are divergent views regarding therapeutic hypothermia (TH) for neonatal hypoxic ischaemic encephalopathy (HIE) in low- and middle-income countries. The aim of this review was to synthesize the literature describing TH for HIE in sub-Saharan Africa by searching Pubmed, Scopus, Google Scholar, and Web of Science from 1996–2023. Thirty records were included: Three surveys, one feasibility study and 26 publications describing 21 cohorts, cooling 1420 babies in South Africa, Uganda, and Ghana. There were five studies recruiting at follow-up, five pilot studies, one randomised controlled trial, one case series, and 10 birth cohorts. Methods and design were highly variable and often inadequate. Two adequately described studies reported survival with normal/mildly abnormal outcome in 71% and 61%, and one representative study of clinic attenders showed 7% cerebral palsy in survivors. Loss to follow-up was 33–36%. Although outcomes were similar to global norms, the high loss to follow-up limits interpretation.